2021
DOI: 10.3171/2020.6.spine191477
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of 90-day return to the emergency room and readmission after elective lumbar spine surgery: a single-center analysis of 5444 patients

Abstract: OBJECTIVEIn the future, payers may not cover unplanned 90-day emergency room (ER) visits or readmissions after elective lumbar spine surgery. Prior studies using large administrative databases lack granularity and/or use a proxy for actual cost. The purpose of this study was to identify risk factors and subsequent costs associated with 90-day ER visits and readmissions after elective lumbar spine surgery.METHODSA prospective, multisurgeon, single-center electronic medical record was queried for elective lumbar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…According to one of these centers' economic analyses, the average postoperative spine ER visit costs around US $2000, whereas the average readmission costs US $7400. [3] Given the significant economic burden, improved patient follow-up and education about medical emergencies may help minimize health care resource utilization by reducing postoperative ER visits following spine surgery. Furthermore, spine procedures are linked with high clinical morbidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to one of these centers' economic analyses, the average postoperative spine ER visit costs around US $2000, whereas the average readmission costs US $7400. [3] Given the significant economic burden, improved patient follow-up and education about medical emergencies may help minimize health care resource utilization by reducing postoperative ER visits following spine surgery. Furthermore, spine procedures are linked with high clinical morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent changes to the American Medicare and Medicaid insurance systems have rewarded hospitals for reducing 90-day postoperative emergency room (ER) visits and penalized them for unnecessary ER visits [ 3 ]. The rates of 90-day postoperative ER visits at 2 major medical centers were 9.4% and 13%, respectively, with postoperative discomfort being the most common reason [ 3 , 4 ]. According to one of these centers’ economic analyses, the average postoperative spine ER visit costs around US $2000, whereas the average readmission costs US $7400.…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons behind these differences between the two cohorts remain largely unknown and might be beyond the scope of this study, it is worth mentioning that these outcome measures might have signi cant clinical and cost implications for patients, physicians, program directors, hospitals and payors [28,37,27,1]. The higher incidence of blood transfusion among orthopedic cohort is of interest since it may represent a potentially modi able practice.…”
Section: Discussionmentioning
confidence: 93%
“…Although this is the first study to identify race as a predictor of 90-day ED visit after PICC line placement, Plate et al 9 recently identified Black race as a predictor of 90-day ED visit after total joint arthroplasty. 9 Similarly, Wiley et al 10 identified Black race as a predictor of 90-day ED visits after lumbar spine surgery. Taken together, this data implies that age and race are important sociodemographic predictors of ED utilization after PICC-line placement.…”
Section: Discussionmentioning
confidence: 97%